(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Currently, the world’s natural gas reserves are 144 trillion. m3, and in Uzbekistan - 2 trillion. m3. Currently, many important products in industry (chlorine-containing solvents, carbon sulfide, cyanide acid, etc.) are synthesized from methane. Catalytic conversion of methane with water vapor is the main method for obtaining hydrogen and synthesis gas. The shortage of oil and oil products requires the creation of alternative methods for obtaining motor fuels, lower olefins and aromatic hydrocarbons. As is known, the synthesis of substances that can replace oil products from natural and associated gases, low molecular alcohols, coal gas and biogas is environmentally and economically feasible. At a time when oil reserves are decreasing, natural gas is of great interest as an alternative fuel in petrochemical production. The current traditional method of converting natural gas into liquid fuels is multi-stage and occurs at high temperatures and high pressures. Currently, promising methods for processing natural gas are its catalytic aromatization and oxycondensation reactions. These processes occur in one stage and at normal atmospheric pressure.